Analysis Of Aceh Bnnp’s Communication Strategy As Strengthening The P4gn Program From A Maqashid Sharia Perspective - Ananda, Fadhillah; Arifin Melayu, Hasnul; Afrian Mustaqim, Riza (Universitas Islam Negeri Ar-Raniry, 2025)
The problem of narcotics abuse and illicit trafficking is one of the most serious problems and continues to grab the attention of the community. In carrying out its duties, BNN requires the support and active role of all components of society, which when viewed more deeply in the Law, the community can support the implementation of BNN's duties, one of which is by becoming a P4GN activist. The abuse and illicit trafficking of narcotics and narcotics precursors (P4GN) as mandated in Law Number 35 of 2009 concerning Narcotics in Article 104 explains that